Optimal sizing of HRES for small sized institute using HOMER - Soni, Vivek Kumar; Khare, Ranjeeta (2014 IEEE 2nd International Conference on Electrical Energy Systems (ICEES), 2014)
Hybrid energy system generally consists of a primary energy source working in parallel with standby secondary energy storage units. Hybrid Renewable energy system (HRES) is a combination of one or several renewable resources such as wind, solar, biomass, small/micro hydro, with other technologies such as batteries and fossil fuel powered diesel generator (for backup) to provide electric power. HRES is an excellent solution for electrification of remote rural areas where the grid extension is difficult and not economical. A hybrid renewable energy system may be used to reduce dependency on either conventional energy or renewable system. This paper gives the design idea of optimized Hybrid Energy System for a certain technical college/remote rural area for a particular site in central India (Bhopal). For this hybrid system, the meteorological data of Solar Isolation is taken for Bhopal (Longitude 77°42' E, Latitude 23°25' N and Altitude 427 m) and the pattern of load consumption of load are studied and suitably modeled for optimization of the hybrid energy system using HOMER software. HOMER (Hybrid Optimization Model for Electric Renewable) is a design model that determines the optimal architecture and control strategy of the hybrid system. Validation of this result is through evolutionary computing such as GA (genetic algorithm). Our objective is selected as minimizing the total capital cost, subject to the constraint of the Loss of Power Supply Probability (LPSP). Studies have proved that the genetic algorithm converges very well and the methodology proposed is feasible for optimally sizing standalone hybrid power systems.